Regulation of maintenance obligations in the European Union / La regulación del derecho de alimentos en la Unión Europea - Rosa Lapiedra Alcamí (Barataria, 2015)
The work deals with one of the most important issues today in the context of family relationships from the international point of view. Indeed, the constant movement of people inevitably implies a rise in mixed family relationships. This, in turn, causes an increase in family conflicts character. In fact, the vast majority of cases, maintenance claims across borders originate in proceedings for divorce or legal separation. If to all this we add the new economic framework arising from the global economic crisis we are experiencing we conclude that the number of complaints worldwide food is very high, hence the great relevance of this work.